Autism in Toddlers: Can Observation in Preschool Yield the Same Information as Autism Assessment in a Specialised Clinic? - Gunilla Westman Andersson; Carmela Miniscalco; Ulrika Johansson; Christopher Gillberg (The Scientific World Journal)
We wanted to know whether preschool observation of children suspected of suffering from autism can provide the same information about core autism symptoms as the Autism Diagnostic Observation Schedule (ADOS) performed in a clinic. Forty 2–4-year-old children (9 girls, 31 boys), referred for assessment of suspected autism spectrum disorder participated in the study. The symptom areas covered by the ADOS algorithm were scored by an education specialist after free-field observation of each child in the preschool without using the prescribed ADOS materials. The ADOS was then completed in a clinic setting by examiners blind to the preschool results. Excellent agreement across results obtained at the two different types/settings of observations was found. The only significant difference found was with regard to spontaneous initiation of joint attention. The present study does not address the issue of whether or not one of the methods used is superior to the other when it comes to determining the “true” level of “autism problems” in these children. However, it is of interest that free-field preschool observation of children with suspected autism using a structured checklist yields very similar information as that obtained at ADOS assessment performed in a clinic setting.